Chronic Temporomandibular Pain Treatment Using Sodium Diclofenac - Kurita Varoli,Fernando (Universidad de La Frontera. Facultad de Medicina, 2012)
This study evaluate spontaneous pain after and before administration of sodium diclofenac, isolated or associated to carisoprodol, acetaminophen and caffeine, in chronic temporomandibular disorders (TMD) patients. Were selected eighteen volunteers, both men and women, between 35-70 years of age (mean age 50 years). The inclusion criteria was masticatory muscle pain, and the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) was used on the diagnose. The selection of treatment for each individual was done by a triple-blind full-randomized crossover methodology. Thus, all patients were submitted to all treatment at different moments, in a non standardized sequence, avoiding tendentious results. The treatments were: A (sodium diclofenac + carisoprodol + acetaminophen + caffeine), B (sodium diclofenac) and C (placebo), all associated with an occlusal splint. Each treatment period was followed by an eleven-day washout. There weren't observed differences between initial and final values of treatments. However, there were statistically significant differences in evaluative and miscellaneous sensorial groups after B treatment; and in sensorial, affective, and total score groups after B and C treatments. Within the limitations of this investigation, we conclude that treatment of muscular TMD patients with sodium diclofenac isolated promoted higher analgesia than treatment with sodium diclofenac more associations or placebo, when associated to an occlusal splint.